Diagnostic accuracy of frozen-section analysis of cancer-containing bladder transurethral resection specimens for the presence of muscularis propria invasion. Issue 7 (14th March 2014) - Goyal, Rajen; Zhu, Bing; Parimi, Vamsi; Lin, Xiaoqi; Rohan, Stephen M
Abstract : Aims: Frozen section (FS) consultation is generally an accurate diagnostic modality. At our institution, we are frequently asked to assess transurethral resection specimens (TURBT) at FS for muscularis propria (MP) invasion by carcinoma. This study documents our experience in evaluating cancer-containing TURBT specimens at FS for MP invasion. Methods: 32 TURBT sent for FS from 2008–2010 were identified. The FS and permanent section (PS) diagnoses were reviewed. Cases excluded from the calculation of test performance included: (1) cases without cancer on FS or PS slides, (2) FS diagnosis deferred, (3) cases without MP on FS and subsequent PS slides. Sensitivity (SEN), specificity (SPEC), positive predictive value (PPV), and negative predictive value (NPV) for identifying MP invasion at FS were calculated. Results: In 6 cases, no cancer was present in FS or PS slides (18%). The FS diagnosis was deferred on 3 cases (9%). In one case (3%) MP was not present in the FS or the subsequent PS slides. Of the remaining 22 cases, 2 false positive and 6 false negative diagnoses of MP invasion were identified. The test performance for FS assessment of MP invasion in TURB were SEN=33%, SPEC=84%, PPV=60%, and NPV=64%. Conclusions: Identifying MP invasion on PS can be difficult, and our results suggest that this is more difficult at FS. Though this study is based on small numbers, our results point to the conclusion that examination of TURBT specimens for MP invasion is best done on PS.